GROWTH PATTERN OF PINUS ROXBURGHII UNDER DIFFERENT REGIMES OF INVASIVE SPECIES IN PANCHASE, NEPAL HIMALAYAS - Dyola, Nita; Bhuju, Dinesh Raj; Kharal, Deepak Kumar; Aryal, Sugam; Gaire, Narayan Prasad; Hitler, Louis (Pakistan Journal of Botany, 2020)
Invasive alien species have taken attention as one of the significant threats to biodiversity worldwide. The ongoing climate change is likely to exacerbate the problem by opening up favorable environments for invasion, putting the ecological, environmental and socio-economic state into stake. The assessment of potential impacts of invasive species on native species is crucial for prevention and mitigation measures. Thus, the current study aimed to assess the impact of invasive species (i.e., Ageratina adenophora Sprengel) on the growth of ecologically important native tree species (i.e., Pinus roxburghii Sargent) in Panchase, Nepal Himalaya Furthermore, it explored the dendroecological approach of Pinus roxburghii to assess the potential impacts of invasive species on its growth. The growth pattern was focused on regeneration, tree radial growth and inter-nodal growth rate of saplings and seedlings of Pinus roxburghii under two different classes of invasion i.e., low and high-density. The study revealed that the density and inter-nodal growth rate of seedlings of Pinus roxburghii declined significantly whereas no significant decline occurred in its saplings with the increase in invasion. However, the saplings showed significant increment in its inter-nodal growth rate with the increase in invasion. In the case of its tree, no such significant impact in the radial growth rate was observed. The novel study using dendroecological approach revealed that the invasive species have differential impacts on the growth of nearby native tree species with higher impacts during the seedling stage compared to the saplings and tree stage.
CRIS-Team WoS Importer:2020-02-28